How incumbents can shape technological choice and market structure – the case of fixed broadband in Europe. Issue 2 (14th March 2016) - Cave, Martin; Shortall, Tony
Abstract : Purpose: – The purpose of this paper is to consider circumstances when technological neutrality in fixed broadband (according firms the power to determine technological choices untrammelled by regulation or the operation of specific incentives) should be adopted. Design/methodology/approach: – The paper reviews the likely effect of such a policy on the competitive structure of fixed broadband markets, taking four case studies as examples. Findings: – The paper finds that choices made by broadband firms with respect to the adoption of fibre to the home versus fibre to the premise, the use of vectoring and the variant of fibre to the home adopted (point to point or point to multipoint) can have a significant effect on the nature of access products which can be provided and thus in the market structure of fixed broadband markets. Access providers can, thus, abridge or foreclose competition in downstream markets. Accordingly, regulators may decide to seek to influence such technological choices to promote competition. But this should be done carefully. Originality/value: – These issues are part of the on-going debate concerning the revision of the European regulatory framework for electronic communications services.